New tools shine a light on solar irrigation in Asia and Africa - Verma, Shilp; Xie, Hua (CGIAR System Organization, 2023)
Solar irrigation holds huge promise for food security, income generation and climate resilience in South Asia and sub-Saharan Africa. But the rise in solar pumping also carries some risks. If pumps are undersized, they will not be able to provide farmers with enough water. If they are oversized, they risk over-abstraction of groundwater and underuse of what are expensive assets. How can we ensure that solar technology is appropriately matched to local conditions and farmers’ requirements?